Four different gene-related cone–rod dystrophy: clinical and genetic findings in six Chinese families with diverse modes of inheritance - Li, Zhen; Cheng, Wanyu; Zi, Feiyin; Wang, Juan; Huang, Xiaoyu; Sheng, Xunlun; Rong, Weining (Frontiers in Genetics, 2023)
Purpose: To investigate pathogenic variants in six families with cone–rod dystrophy (CORD) presenting various inheritance patterns by using whole-exome sequencing (WES) and analyzing phenotypic features. Methods: A total of six families with CORD were enrolled in Ningxia Eye Hospital for this study. The probands and their family members received comprehensive ophthalmic examinations, and DNA was abstracted from patients and family members. Whole-exome sequencing was performed on probands to screen the causative variants, and all suspected pathogenic variants were determined via Sanger sequencing. Furthermore, co-segregation analysis was performed on available family members. The pathogenicity of novel variants was predicted using in silico analysis and evaluated according to the American College of Medical Genetics and Genomics (ACMG) guidelines. Results: Of the six families, two families were assigned as X-linked recessive (XL), two families were assigned as autosomal recessive (AR), and two families were assigned as autosomal dominant (AD). Pathogenic variants were detected in CACNA1F in two X-linked recessive probands, among which family 1 had a hemizygous frameshift variant c.2201del (p.Val734Glyfs*17) and family 2 had a hemizygous missense variant c.245G>A (p.Arg82Gln). Both probands had high myopia, with fundus tessellation accompanied by abnormalities in the outer structure of the macular area. The homozygous splice variant c.2373 + 5G>T in PROM1 and the homozygous nonsense variant c.604C>T (p.Arg202Ter) in ADAM9 were detected in two autosomal recessive families of the probands. Both probands showed different degrees of atrophy in the macular area, and the lesions showed hypofluorescence changes in autofluorescence. The heterozygous variation in CRX c.682C>T (p.Gln228Ter) was detected in two autosomal dominant families. The onset age of the two probands was late, with better vision and severe macular atrophy. According to ACMG guidelines and the analysis of online in silico tools, all variations were labeled as potentially harmful or pathogenic. Conclusion: Pathogenic variants in CACNA1F, PROM1, ADAM9, and CRX genes were identified in six families affected by the diverse inheritance patterns of CORD. Furthermore, the potential impact of the nonsense-mediated decay (NMD) mechanism on the manifestation of CORD phenotypes was examined and addressed. Simultaneously, the spectrum of pathogenic variants and clinical phenotypes associated with the CORD gene was extended.